Designing spaces for natural ventilation : an architect's guide - Passe, Ulrike; Battaglia, Francine (New York ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2015)
Buildings can breathe naturally, without the use of mechanical systems, if you design the spaces properly. This accessible and thorough guide shows you how in more than 260 color diagrams and photographs illustrating case studies and CFD simulations. You can achieve truly natural ventilation, by considering the building's structure, envelope, energy use, and form, as well as giving the occupants thermal comfort and healthy indoor air. By using scientific and architectural visualization tools included here, you can develop ventilation strategies without an engineering background. Handy sections that summarize the science, explain rules of thumb, and detail the latest research in thermal and fluid dynamics will keep your designs sustainable, energy efficient, and up-to-date.
Foreword by Sue Roaf. Acknowledgements. Introduction. Part 1: Theories and Scientific Background 1. The Importance of Space for Natural Ventilation 2. The Physics of Air Flow 3. The Importance of Fresh Air for Occupant's Health 4. Natural Ventilation and Climate 5. Inherited Spatial Archetypes for Natural Ventilation 6. Natural Ventilation and Thermal Comfort Part 2: Parameters 7. Pressure as Indicator 8. Spatial Strategies / Space-Induced Air Movement 9. Facade as Filter: From Windows to Curtain Walls to Adaptive and Smart Skins 10. Control of Natural Ventilation Part 3: Making Air Visible: Complex Science Summarized for Architects and Designers 11. Overview of Methods for Calculation and Simulation 12. Computational Fluid Dynamics Conclusion. Notes. Bibliography. Image Credits. Index
Includes bibliographical references (pages 312-324) and index.
ARC
Trim Education
Keywords: Natural ventilation; Winds and architecture; Architecture and climate; Architecture